1988
DOI: 10.2527/jas1988.66112876x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Osmotic Pumps for Subcutaneous Infusion of Growth Hormone-Releasing Factors in Steers and Wethers

Abstract: Osmotic pumps were evaluated for 7-d delivery of growth hormone-releasing factor (GRF). In Exp. 1, 12 steers weighing 253 kg received hGRF(1-29)NH2 in H2O at rates of 0, 3, 30 and 300 pmol.h-1.kg-1. Pumps were implanted s.c. on d 0 and removed at 1200 on d 7. Blood samples were drawn at 20-min intervals from 0800 to 1200 on d -1, 1, 3, 5, 7 and 9. Growth hormone levels were not altered by GRF treatment (P greater than .05). Solubility and volume limitations render hGRF(1-29)NH2 delivery via osmotic pumps probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…AUCs for GH response curves increased in GRF-treated bovines (Moseley et al 1984, Petitclerc et al 1987, Enright et al 1989, 1993, Lapierre et al 1990, Simpson et al 1992, Ringuet et al 1994, Kazmer & Zinn 1998, Kazmer et al 2000, Wiener et al 2000, ovines (Hart et al 1985, Della-Fera et al 1986, Kensinger et al 1987, Wheaton et al 1988, Byrem et al 1989, Beermann et al 1990, Godfredson et al 1990, and swine (Takano et al 1985, Dubreuil et al 1990) over placebo. The present study revealed similar observations in GRF-administered growing Murrah buffaloes.…”
Section: Plasma Gh Changes Associated With Grf Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…AUCs for GH response curves increased in GRF-treated bovines (Moseley et al 1984, Petitclerc et al 1987, Enright et al 1989, 1993, Lapierre et al 1990, Simpson et al 1992, Ringuet et al 1994, Kazmer & Zinn 1998, Kazmer et al 2000, Wiener et al 2000, ovines (Hart et al 1985, Della-Fera et al 1986, Kensinger et al 1987, Wheaton et al 1988, Byrem et al 1989, Beermann et al 1990, Godfredson et al 1990, and swine (Takano et al 1985, Dubreuil et al 1990) over placebo. The present study revealed similar observations in GRF-administered growing Murrah buffaloes.…”
Section: Plasma Gh Changes Associated With Grf Administrationmentioning
confidence: 99%
“…In another study (Ringuet et al 1994), twice daily s.c. administration of GRF for 246 days at 5 mg/kg body weight in Holstein dairy heifers resulted in an increase in GH concentrations throughout the trial and all heifers responded to GRF until the last day of the experiment, suggesting that GRF may be used to induce daily GH release without loss of responsiveness over an extended period of time in young dairy heifers. Similarly, exogenous intermittent administration of GRF enhanced secretion and circulating concentrations of GH in ovines without them becoming refractory to GRF (Hart et al 1985, Della-Fera et al 1986, Kensinger et al 1987, Wheaton et al 1988, Byrem et al 1989, Beermann et al 1990, Godfredson et al 1990). Chronic repeated administration of GRF in growing pigs did not induce desensitization of somatotroph cells.…”
Section: Plasma Gh Changes Associated With Grf Administrationmentioning
confidence: 99%
“…Accordingly, numerous experiments have shown the efficacy of synthetic GHRH (1-29)-NH z in stimulating GH release in humans (4) and experimental animals such as rats (24), and lambs (2). In the last paper, exogenous sc intermittent administration of GHRH increased circulating GH concentrations (2), and the same peptide was found to raise G H levels when delivered by sc osmotic pumps (28). Therefore, this GHRH preparation seems to be appropriate for investigating dynamic changes of GH release and also to be used as a potential alternative to exogenous GH administration in the sheep.…”
mentioning
confidence: 99%